(untitled) (Conferencea, 2023)
Agrotourism’s evolution is guided by modern consumers’ emphasis on "ecological cleanliness" across the residence, food, and leisure. This shift prompts a new approach to leisure organization, transitioning from the traditional "sea-sun-sand" to a nuanced "lore-landscape-leisure" model, accentuating personalized services. Agrotourism strategically caters to small groups, aligning with these preferences. Its success hinges on meeting the needs of this emerging consumer base while factors like increased mobility, urban stress, and rural allure propel its growth. This abstract explores the theoretical underpinnings of agrotourism, emphasizing consumer-driven trends shaping its trajectory across European landscapes.